Apport des Instruments de la Conférence de La Haye au droit des affaires dans l’espace OHADA - Monsenepwo Mwakwaye, Justin (Junges Afrikazentrum, 2016)

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Plaidoyer pour l’adoption du crédit-bail en Afrique en droit OHADA - Pohé Tokpa, Denis (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2016)
Il s’agit de revêtir le manteau du législateur africain pour rechercher le profil idéal de l’un des contrats d’affaires le plus utilisé aujourd’hui dans la pratique en Afrique mais sans faire forcément l’objet d’une réglementation adaptée. Lors de la dernière conférence des chefs d’Etat des pays membres de l’OHADA au Burkina Faso en janvier 2014, le crédit-bail a été retenu entre autres contrats d’affaires comme l’un des principaux axes d’un projet d’Acte uniforme. Dans les pays d’Afrique où l’épargne locale est quasi-inexistante, le crédit- bail est un moyen incontournable pour les TPE et PME disposant de très peu de fonds propres et qui ont difficilement accès au crédit bancaire, faute de garanties suffisantes, pour développer leur activité économique.

La fonction de l’agent immobilier dans la vente d’immeuble achevé - Divoux, Jean-Pierre (Université de Lorraine, 2016)
Devant les remarques critiques dont fait l’objet la profession d’agent immobilier, il a paru intéressant à un agent immobilier à la retraite de faire le point sur la fonction de l’agent dans la vente d’immeuble achevé. Le sujet ne saurait se limiter au seul examen des rapports contractuels compliqués qui se nouent entre le vendeur, l’acheteur et l’agent immobilier. En effet, en menant à bien les projets de vente ou d’achat que lui confient ses clients, l’agent ne se contente pas d’accomplir la tâche d’un intermédiaire fiable sur un marché dont il a une bonne connaissance ; il devient véritablement un rouage structurant du marché immobilier. Naturellement, après l’étude du rôle de l’agent immobilier sur le marché immobilier, c’est son rôle dans le processus qui conduit à la conclusion du contrat de vente qui mérite de retenir l’attention, et cela depuis le moment où quelqu’un lui confie un mandat, qu’il soit de vente ou de recherche, jusqu’au moment où l’une des parties à la vente, mécontente de l’opération, se retourne contre l’agent immobilier
Keywords: Agents immobiliers; Droit immobilier; Immeubles; Immobilier; Vente et transmission; Vente immobilière

L’ordre juridique communautaire "OHADA" et les enjeux d’intégration du droit des affaires - Mikponhoue, Hervis Igor Cariol (Université de Perpignan Via Domitia, 2016)
Au lendemain de leur accession à l'indépendance dans les années 1960, les pays d'Afrique Francophone étaient dotés d'un système de droit privé étroitement dérivé de celui de l'ex-puissance coloniale. Pendant près de deux décennies, ces États ont fait évoluer séparément leurs législations conformément à l'expression de la souveraineté nationale même si la volonté d'unifier le droit en Afrique était matérialisée par des tentatives sous-régionales ayant peu abouti.Aujourd’hui, l’Organisation pour l’Harmonisation en Afrique du droit des Affaires(OHADA), créée depuis 1993 à Port-Louis œuvre pour une harmonisation du droit desaffaires en Afrique. Par l’adoption de ses divers actes uniformes, elle a su harmoniser voire uniformiser au plan communautaire les domaines essentiels du droit des affaires, notamment le droit commercial, le droit des sociétés et le droit des sûretés. Dans sa perspective d’intégration, elle envisage aussi d’énormes chantiers de codification afin d’étendre sa communauté à d’autres Etats encore réticents à une perte de leur souveraineté au profit d’une instance d’intégration et d’harmonisation du Droit des affaires.Dans la logique des objectifs poursuivis, nos premiers travaux de terrain ont porté sur l’ERSUMA étant donné qu’elle dispose d’une documentation très fournie sur l’OHADA, et que cette institution dont le rôle consiste à former les magistrats des divers Etats membres sur les textes communautaires, est ainsi le principal outil de vulgarisation des actes uniformes et des traités de l’organisation. Elle est donc l’une des instances les plus actives et les plusindispensables de l’OHADA.Retenons que cette perspective d’intégration de l’OHADA soulève encore d’énormesinterrogations relatives à la finalité des objectifs de l’Organisation, qui s’inscrit plus dans une perspective d’uniformisation que d’harmonisation comme le laisserait penser sa dénomination ; ajouté à l’épineuse question de la criminalisation des infractions en droit des affaires en Afrique et surtout à l’existence ou non d’un ordre juridique pour l’OHADA. Aussi, d’autres points importants, et diverses autres problématiques liées à l’intégration africaine du droit des affaires, ne présagent pas encore d’un avenir glorieux pour l’Organisation. Following their accession to independence in the 1960s, the countries of Francophone Africa were equipped with a system of private law closely derived from that of the former colonial power. During about two decades, these States have separately evolved their legislation in accordance with the expression of national sovereignty even if the desire to unify law in Africa was marked by sub regional attempts little successful. Today, the Organization for the Harmonization of Business Law in Africa (OHADA), created 1993 since in Port Louis works for business law harmonization in Africa. With the adoption of its various uniform acts, it has managed to harmonize or standardize at community level the essential areas of business law, including business law, corporation law and reliability law. In its perspective of integration, it is also considering consolidation sites in order to expand its community in other States which still reluctant to a loss of sovereignty for the benefit of an instance of integration and harmonization of business law. Let us remember that this OHADA integration perspective still raises huge questions regarding the purpose of the Organization's objectives, which fits more in a perspective of standardization over harmonization as its name would suggest; added to this sensitive issue of offenses criminalization in Business Law in Africa. Also, other important points and various issues related to African integration, which do not portent a glorious future for the Organization.
Keywords: Accountability or liability; Acte uniforme; Afrique francophone; Droit des affaires; Harmonisation; Harmonization; Integration's reform of OHADA; Reformes d’intégration OHADA; Responsabilité; Straight of business; Unification internationale; Uniform Act

Essai sur le formalisme contemporain dans la protection du consentement contractuel - Fortich, Silvana (Université Paris 2, 2016)
En matière de formation des contrats, le consentement de la partie qui s’oblige est soumis au principe de liberté des formes. Par exception, la volonté doit adopter une certaine forme contractuelle pour s’extérioriser. Face à l’évolution du droit des contrats et à la nécessité de combattre les déséquilibres contractuels propres aux rapports contractuels actuels, le formalisme expérimente un processus de revitalisation et de renaissance en droit contemporain dont la finalité principale consiste à protéger le consentement contractuel des parties au contrat. Cela rend indispensable l’analyse des fondements du formalisme et de son rôle dans la protection du consentement contractuel en droit contemporain, à travers la révision transversale de ses nouvelles manifestations, principalement en matière du droit de la consommation et du commerce électronique ; pour constater finalement ses véritables effets et conséquences en matière du droit des contrats. In contract law, the agreement of the parties is ruled by the freedom of choice of forms of contract. In this way, contracts are signed by the mere consent of the parties, and there is a freedom regarding the ways for its externalization. Despite this, the evolution of contract law and the need to combat specific contractual imbalances of contractual relationships, formalism is experiencing a revitalization process and a rebirth in contemporary law, with the main purpose to protect the contractual consent. For these reasons it is necessary to analyze the role of formalism in the protection of contractual consent, reviewing its new manifestations, mainly in the field of consumer and commercial law ; finally finding its true effects and consequences in contract contemporary law.
Keywords: Agreement; Consensualism; Consensualisme; Consentement; Consentement (droit); Consommateur; Consumers; Contract; Contrat; Contrats de consommation; Formalism; Formalisme; Formalité; Formalités (droit); Forms; Freedom; Information; Liberté; Liberté contractuelle; Mentions; Parties; Volonté

تأثير تغير الظروف على استقرار الثمن في عقود التجارة الدولية - موكه, عبد الكريم (جامعة مولود معمري, 2016)
Le thème de recherche porte sur la clause du prix en matière des contrats du commerce international, Cette étude qui tente d’y contribuer, porte essentiellement sur le domaine des pratiques contractuelles en droit des contrats du commerce international de longue durée, elle se propose de chercher les différentes techniques conventionnelles et juridiques pouvant maintenir la stabilité du prix et de chercher un moyen permettant de sauvegarder l’équilibre contractuel en dépit d’un bouleversement des données initiales causé par la survenances de circonstances nouvelles. Le prix est un élément essentiel dans la vie du contrat du commerce international sur lequel se focalise le consentement. Il est le centre de gravité du contrat international, mais vu la durée d’exécution des contrats internationaux et les différentes circonstances -imprévision ,force majeure et bouleversement économique- qui entravent la bonne exécution des clauses du contrat dont il est le prix, la modification et l’adaptation du prix devienne une nécessité imposée par les pratiques contractuelles et la jurisprudence arbitrale, cette révision ou réadaptation causé par l’impact de nouvelles circonstances imprévues permettra de sauver le contrat de sa disparition prématurée. Ainsi, le prix change de statut est devient élément secondaire qui varie en vertu des nouvelles circonstances, il remplit la fonction de protectionnisme pour maintenir la stabilité des contrats du commerce international.

Réflexion critique sur l’attractivité du groupement d’intérêt économique (GIE) en droit de l’Organisation pour l’harmonisation du droit des affaires en Afrique (OHADA) - Dewedi, Éric (Les Cahiers de droit, 2016)
En droit de l’Organisation pour l’harmonisation du droit des affaires en Afrique (OHADA), la création du groupement d’intérêt économique (GIE) représente une opportunité laissée aux entreprises de mettre en commun leurs moyens pour accroître leurs activités économiques. Mais paradoxalement, le GIE n’est pas très utilisé par ses destinataires. Il fait ainsi l’objet d’un silence des acteurs qui conduit à s’interroger sur son attractivité. Il apparaît à l’analyse que l’un des attraits du GIE est voulu par la loi, mais qu’il est fortement compromis. En effet, les membres disposent d’une très grande liberté dans la constitution et le fonctionnement du GIE. Cette liberté n’a de limites que dans quelques règles impératives tournées vers la protection des tiers, notamment l’inopposabilité aux tiers des clauses limitatives des pouvoirs de l’adminsitrateur ou des administrateurs et la responsabilité indéfinie et solidaire des membres par rapport aux dettes du GIE. C’est cette responsabilité indéfinie et solidaire des membres relativement aux dettes du GIE qui compromet sérieusement l’attractivité de ce dernier. Il est cependant possible de rendre le GIE plus attractif par l’utilisation des conventions qui permettent à ses membres d’accorder des avantages particuliers aux nouveaux membres par contrat et aussi d’exclure la solidarité aux dettes par des accords avec les tiers contractants. Ces conventions pourraient assurer la sécurité du crédit par le recours aux garanties.

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

La notion de bail professionnel en droit OHADA et ses implications sur la théorie générale du fonds de commerce - Eyango Djombi, André Desmonds (Juridical Tribune : Review of Comparative and International Law, 2016)
The last reform of the Uniform Act on General Commercial Law OHADA reconsidered several pieces of commercial law. The concept of leasing has not been spared. She, who was accompanied by the "commercial" substantive, has been transformed into "commercial lease". Question of style or simple semantics? Certainly not, because the legislature in 1997, had not previously dared revise the designation commercial lease that no longer fit with the extension of the beneficiaries he had devoted himself. With the reform of December 2010, the institution of the lease has just renamed. Parliament also confirmed the extension of the scope of economic actors involved in the protection of the lease. The regime of former Uniform Act was therefore not fully extended, particularly since we noted another significant change in the new text. Contrary to former Article 69 which devoted two cumulative criteria necessary for the implementation of the lease of the regime, including the situation in a populated city of more than 5,000 people and membership of local under lease to a designated class2, the new text retains a single criterion, that of belonging to a local specific category. This mutation disrupts some basics of goodwill theory. Indeed, with the increasing scope of lessees, there is a sliding protection to professional trader. This causes result in a substitution of the lease of the foundation that passes from customer to the profession. The loss of the privileged place of business customers coupled with doctrinal and jurisprudential developments in the theory of civil customers, argue for an assimilation of the different customer categories.
Keywords: Bail; Business assets; Business lease; Commercial Law; Fonds de commerce

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)

Le contentieux de l’immatriculation du commerçant au registre du commerce et du crédit mobilier en droit OHADA - Kamnang Komguep, Irène Flore (Revue de droit de l'Université de Sherbrooke, 2016)
En droit des affaires, le commerçant est soumis à plusieurs obligations au rang desquelles figure l’immatriculation au RCCM. Celle-ci constitue une mesure de publicité légale dont l’accomplissement vaut, sauf exception, reconnaissance de la qualité de commerçant à l’égard de la personne physique et déclaration de la société commerciale à l’état civil. En plus de ces résultats immédiats, l’immatriculation a pour but d’assurer la sécurité des transactions commerciales. C’est à juste titre que le droit a prévu et organisé le contentieux de l’inexécution de l’obligation d’immatriculation et celui relatif aux incidents de la procédure d’immatriculation. La question qui se pose est celle de savoir si l’intervention du juge contribue effectivement à vaincre non seulement la négligence ou l’inertie des assujettis, mais aussi les obstacles à l’attribution d’un numéro d’immatriculation. Si l’organisation des différents axes du contentieux de l’immatriculation du commerçant au RCCM paraît satisfaisante, les suites de l’intervention du juge demeurent quant à elles perfectibles à certains égards. Il est nécessaire d’envisager des pistes de solutions tant en ce qui concerne le traitement du contentieux de l’inexécution de l’obligation d’immatriculation que celui des incidents de la procédure d’immatriculation.
Keywords: Crédit mobilier; Immatriculation; Registre du commerce

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.